The genus Platylomia Stål, 1870 (Hemiptera: Cicadidae) from Vietnam, with description of one new species and key to species - Thai, Pham Hong; Constant, Jérôme (Academia Journal of Biology, 2015)
The Platylomia radha species group is proposed within the genus Platylomia Stål, which includes one new species, Platylomia duffelsi sp. nov., from the north Vietnam. Synonymic lists for the four species of Platylomia from Vietnam are provided. A key to the four Platylomia species: P. bocki (Distant), P. duffelsi sp. nov., P. malickyi Beuk, and P. operculata Distant from Vietnam is provided. Photos of the adult, illustrations of the male genitalia, a distribution map and biological data are also given.